Burnout: Caring for critically ill and end‐of‐life patients with cancer. Issue 2 (22nd July 2019) - Pattison, Natalie; Droney, Joanne; Gruber, Pascale
Abstract: Background: Critical care and palliative care professionals treat and support seriously ill patients on a daily basis, and the possibility of burnout may be high. The consequences of burnout can include moral injury and distress, and compassion fatigue, which are detrimental to both care and staff. Aims and objectives: To explore the incidence of moral distress in areas at high risk of burnout in a large cancer centre and to explore possible measures for addressing moral distress. Design: A cross‐sectional survey. Methods: The Maslach Burnout Inventory was administered to critical care, critical care outreach, and palliative care teams in a specialist tertiary cancer centre. Open questions on supportive measures were also included. Burnout data were categorised into three domains of emotional exhaustion, depersonalization and personal accomplishment, and free‐text analysis was conducted on the open‐question data. Results: A total of 63 professionals responded across the teams (45% response rate). A low level of burnout was observed in the emotional exhaustion domain; depersonalization was higher in the critical care professionals; and overall, personal accomplishment was higher than normative scores. Free‐text analysis highlighted three categories of responses: Debriefing, Managing emotional well‐being, and Valuing individuals. There was a need to proactively recognize issues; undertake more debriefs; and open forums regarding cases, particularly with difficult deaths. Engaging all professionals, support to deal with families, and mandatory moral distress and resilience training were suggested, alongside a focus on team building through external activities such as group relaxation sessions and walks. Conclusions: This study demonstrated a relatively low incidence of emotional exhaustion and depersonalization, and a slightly higher sense of personal accomplishment than normative scores despite staff working in an environment where high levels of burnout were expected. Relevance to clinical practice: Staff highlighted possible solutions to reduce burnout, which included debriefing, managing emotional well‐being, and valuing individuals.